SOURCES OF LIPIDS IN DIETS FOR SILVER CATFISH (Rhamdia quelen) JUVENILES - Ricácio Luan Marques GOMES; Evandro Bilha MORO; Bruno dos Santos SOSA; Danielle Zanerato DAMASCENO; Mariana Lins RODRIGUES; Fabio BITTENCOURT (Boletim do Instituto de Pesca)
The purpose of this study was to evaluate different lipid sources in diets for silver catfish juveniles regarding aspects of productive performance, centesimal composition, hepatic histology, biochemical responses, and oxidative stress. A total of 300 juveniles with an initial mean weight of 18.45 Â± 1.22g were distributed in 20 net-pens of 1m3, arranged in a 200 m2 masonry tank, for a period of 90 days. The experimental diets were isoprotein (29.05% digestible protein) and isoenergetic (3,250 kcal.kg-1), containing different sources of oils (soybean, sunflower, fish, canola and olive) at a concentration of 3.0%. The animals were distributed in a completely randomized design, with five treatments and four replicates. The data were submitted to ANOVA, and the means, when significant, were compared by the Tukey test at 5% significance level. Visceral fat index was higher for fish fed diets containing sunflower oil (P<0.05). No differences (P>0.05) were observed for the variables of productive performance, centesimal composition, and blood biochemistry. A difference (P<0.05) was observed in hepatic histology, where the treatment with soybean oil had a higher number of hepatocytes. The animals fed with fish oil had a higher TBARS lipid peroxidation and a higher GST enzyme activity (P<0.05). Therefore, the different lipid sources can be used to feed this species without any damage to productive performance. It is not advisable to include sunflower oil, as it provides greater deposition of visceral fat.